Socio-cultural environment as a factor influencing perception of overweight and obesity - Olišarová, Věra; Tóthová, Valérie; Dolák, František (Magyar Egészségügyi Szakdolgozói Kamara, 2014)
The increase of incidence of overweight and obesity is a wolrldwide problem. Its therapy, as well as prevention, require holistic perception of the issue. The results demonstrate that these diseases cannot be perceived separately but from the perspective of health impact. The socio-economic area, the influences of ethnicity, cultural particularities and a lot of other factors must be considered. This article is focusing on the relation between the socio-cultural environment and perception of overweight and obesity as factors which can be directly reflected sith preventive and therapeutic measures. The results show that ethnicity, cultural particularities, acculturation level, social status etc. are factors that influence the incidence of the relevant diseases to some degree. At present, there is lack of sufficient research studies which support the creation and implemantation of culturally adequate interventions not only on the territory of the Czech Republic but worldwide.
Sociokulturní prostředí jako faktor ovlivňující vnímání nadváhy a obezity
Keywords: overweight; obesity; prevention; ethnicity; gypsy; enequalities in health; nadváha; obezita; prevence; etnicita; Romové; nerovnosti ve zdraví